2013
DOI: 10.1007/s13201-013-0082-5
|View full text |Cite
|
Sign up to set email alerts
|

Removal of arsenic(III) and arsenic(V) on chemically modified low-cost adsorbent: batch and column operations

Abstract: Batch and column operations were performed utilizing thioglycolated sugarcane carbon (TSCC), a lowcost adsorbent, to remove As(III) and As(V) from aqueous systems. Under optimized batch conditions, the TSCC could remove up to 92.7 and 91.4 % for As(III) and As(V), respectively. An artificial neural network model showed the validity of TSCC as a preferable adsorbent for arsenic [As(III) and As(V)] removal in batch studies. In column operations, removal efficiency increases with increase in influent arsenic conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…This is due to the adsorption of almost all As(V) onto the adsorbent surface and attaining of equilibrium between the As(V) adsorbed to the adsorbent and those As(V) left in the solution. The results of this study are the following similar type of pattern reported as findings by other researchers (Li et al 2012;Roy et al 2013). The optimum value of adsorbent dosage was 0.75 g L -1 and for the rest of the experiment this value was used.…”
Section: Effect Of Adsorbent Dosagesupporting
confidence: 92%
See 1 more Smart Citation
“…This is due to the adsorption of almost all As(V) onto the adsorbent surface and attaining of equilibrium between the As(V) adsorbed to the adsorbent and those As(V) left in the solution. The results of this study are the following similar type of pattern reported as findings by other researchers (Li et al 2012;Roy et al 2013). The optimum value of adsorbent dosage was 0.75 g L -1 and for the rest of the experiment this value was used.…”
Section: Effect Of Adsorbent Dosagesupporting
confidence: 92%
“…Commercial activated carbons are expensive and it is the main drawback of using this adsorbent in all the application sectors (Roy et al 2013). Recently, some of the low cost compounds such as zirconium oxide-coated marine sand, chir pine sawdust, bagasse fly ash, clay and magnetic chitosan-bamboo sawdust composites were employed while some of the biomasses were also used to remove arsenic from water (Khan and Sing 2010;, Khan and Nazir 2015Ali et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a low adsorption capacity for adsorbents with a high surface area was observed by Roy et al [111] on thioglycolated sugarcane carbon (TSCC) as an adsorbent for arsenic removal. TSCC has a surface area of 5690 m 2 /g.…”
Section: Adsorption Isotherm Studies On As(iii) and As(v)mentioning
confidence: 71%
“…TSCC has a surface area of 5690 m 2 /g. The maximum reported As(III) and As(V) removal by TSCC was 85.01 and 83.82 g/g, respectively, with an initial arsenic concentration of 1,500 g/L [111].…”
Section: Adsorption Isotherm Studies On As(iii) and As(v)mentioning
confidence: 95%
“…the decreasing of the EBCT, is expected as the adsorption capacity is directly proportional to the contact time. Increase of the k th values with increasing the discharge rate of effluent indicate the decrease of mass transport resistance and axial dispersion [33] .…”
Section: Thomas Modelmentioning
confidence: 99%